CLEC12A-directed immunocytokine with target cell–restricted IL-15 activity for treatment of acute myeloid leukemia - Klimovich, Boris; Anton, Leonard; Jung, Jinwon; Lim, Yangmi; Lee, Bora; Won, Jonghwa; Zekri, Latifa; Chashchina, Anna; Pflügler, Martin; Heitmann, Jonas S.; Jung, Gundram; Salih, Helmut R. (Frontiers in Immunology, 2025)
Despite recent advancements, acute myeloid leukemia (AML) remains a therapeutic challenge. While monoclonal antibodies (mAbs) leveraging natural killer (NK) cells through antibody-dependent cellular cytotoxicity show great potential, none have gained clinical approval for AML. Immunocytokines have emerged as a promising strategy to overcome the limited efficacy of therapeutic antibodies. IL-15 stimulates activation, proliferation cytotoxic activity of NK cells, but its clinical use is prevented by short half-life, poor accumulation in the tumor, and toxicity due to systemic off-target immune activation. Here we report on the generation and preclinical characterization of modified immunocytokines consisting of an Fc-optimized CLEC12A (CLL-1) antibody fused to an IL-15 moiety with E46K mutation. The mutation abrogates binding to IL-15Rα, thereby enabling substitution of physiological trans-presentation by target binding and thus conditional IL-15Rβ/γ stimulation to reduce systemic toxicity. An optimal CLEC12A binder was selected from a range of murine mAbs, based on analysis of AML cell lines and leukemic cells from patients. This antibody was then used to construct an immunocytokine (MIC12) that subsequently was characterized functionally. Analysis of NK cell activation, cytokine release, proliferation and anti-leukemia reactivity demonstrated that MIC12 induced superior target cell killing and NK cell expansion compared to Fc-optimized CLEC12A antibody, with efficacy being dependent on target antigen binding. Our results show that novel immunocytokines with conditional IL-15 activity are capable of inducing potent NK cell responses against AML cells and identify MIC12 as promising therapeutic candidate for leukemia treatment.